2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610981
|View full text |Cite
|
Sign up to set email alerts
|

An arc-length warping algorithm for gesture recognition using quaternion representation

Abstract: This paper presents a new algorithm, called Dynamic Arc-Length Warping algorithm (DALW) for hand gesture recognition based on the orientation data. In this algorithm, after calculating the quaternion for each orientation measurement, we use DALW algorithm to obtain a similarity measure between different trajectories. We present the benefits of using quaternion alongside the implementation of Dynamic Arc Length Warping to present an optimized tool for gesture recognition.We show the advantages of this approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, solely leveraging 3D positions as input channels led to poor segmentation and classification performance. In the same way, Cifuentes et al [41] used only quaternion information to retrieve operator gestures (i.e., intention could be correlated to orientation as well). Based on this analysis, we concluded that the operators intentions could be determined using rigid transformation data.…”
Section: Discussion a Kinematic Channels Impactmentioning
confidence: 99%
“…However, solely leveraging 3D positions as input channels led to poor segmentation and classification performance. In the same way, Cifuentes et al [41] used only quaternion information to retrieve operator gestures (i.e., intention could be correlated to orientation as well). Based on this analysis, we concluded that the operators intentions could be determined using rigid transformation data.…”
Section: Discussion a Kinematic Channels Impactmentioning
confidence: 99%